The effects of the civil responsibility of the hosting provider on the Internet in the Jordanian law- A comparative study - Bani Hamad, Abdelsalam Ahmad (Revue jurisprudence; Vol. 11 No 02 (2019): مجلة الاجتهاد القضائي, 2019)
This research, which is a comparative study, highlights the civil responsibility and the obligation of the hosting provider (fournisseur d’hébergement) on the Internet in the Jordanian law. The law register has newly organized a private law about it. “ The electronic translation law NO. (15) Of the (2015). In comparative translation to other Arab and foreign countries the newly electronic law is devoid of any references that determines the nature of the civil liabilities of the hosting provider. It has to be developed according to the revolution of the Internet.